Socialismo, cooperativismo e economia solidária no pensamento de Paul Singer - Pandeló, Fernando Rodrigues (2010)
The objective of this material is to present, discuss and analyze the theoretical work of Paul Israel Singer regarding the solidarity economy . The author attributes a significant role to the cooperatives, while rejecting the revolutionary political struggle of the proletariat by the conquest of state power as a strategy for the implementation of socialism. We demonstrate through this study that the fundamental thesis about the transition of the socialist, remained in his theoretical work on the "solidarity economy", specifically: 1) the rejection of the proletariat‟s revolutionary political struggle; 2) and the conditioning of the political struggle (for the democratization) in relation to the economic struggle for self-production. In the theoretical works about the solidarity economy , in opposition to the revolutionary socialist theory, the author reinforces the utopian socialist concept and transforms the struggle for self-production within capitalism into a socialist struggle